A new species of Tabernaemontana (Apocynaceae; Rauvolfioideae: Tabernaemontaneae) from Mexico - Alvarado-Cárdenas, Leonardo O.; Santillán, Vinisa Saynes (Phytotaxa, 2018)
A new species of Tabernaemontana from south-eastern Mexico is described and illustrated. Tabernaemontana riverae is separated from all known species of the genus by its long elliptic–lanceolate sepals and infundibuliform corolla. The new species is endemic to Mexico and only observed in the states of Oaxaca, Tabasco, and Veracruz. With this addition, Tabernaemontana is represented in Mexico by 15 species, six of them endemic. These numbers highlight Mexico as a diversity center for the genus. We propose a conservation status for the new species and provide a key to the Mesoamerican species of Tabernaemontana with leaf-like sepals.